PENGARUH PROGRAM SERTIFIKASI PERIODE 2009/2011 TERHADAP PENINGKATAN KINERJA GURU DAN MUTU PENDIDIKAN PADA TINGKAT SEKOLAH MENENGAH KEJURUAN NEGERI (SMKN) DI KOTA JEMBER TAHUN AJARAN 2012/2013 - Ruliyanti Kusumawardani (Jurnal Ekonomi Akuntansi dan Manajemen, 2014)
Research on "The Effect of Certification Program Period 2009/2011 Against Teacher Performance Improvement and Quality Education At Level Vocational High School (SMK) in Jember city in Academic Year 2012/2013".The purpose of this study is 1. For to test and analyze the effect of teacher certification program period 2009/2011 to increase teacher performance level Vocational High School (SMK) in Jember City school year 2012/2013. 2. To examine and analyze the effect of the certification program period 2009/2011 on educational quality level Vocational High School (SMK) in Jember City school year 2012/2013. 3. To determine and analyze the effect on educational quality teacher performance level Vocational High School (SMK) in Jember City school year 2012/2013. Populations are teacher subject areas PNS National Final Examination (UAN) consisting of Indonesian studies, study Mathematics, English studies at five vocational high schools in the city of Jember who has received benefits or a professional certification program that has escaped the period 2009/2011. Number of certified teachers as much as 137 people. Techniques or sampling method used is proportional sampling design in this study is included in the explanatory describes the relationship between two or more variables. The results showed that certification has a significant positive effect on the performance and quality of education. This is evident from the results of the analysis, the higher the teacher pemahan objectives, concepts, and maanfaat teacher certification, then diaharapkan increasing teacher performance that will have an impact on the quality of education. Keywords: Certification, Performance Teacher, Quality of Education